Preparation method and application of composite material for resisting periodontitis microbial infection
By hydrothermal synthesis of Bi2S3 and graphene oxide composites, near-infrared light activates carriers to generate reactive oxygen species, solving the secondary infection and drug resistance problems in the treatment of periodontitis microbial infection, and achieving efficient clearance and biology Compatibility provides new treatments.
Patent Information
- Application Number
- CN202411609502.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing treatments for periodontitis microbial infection, such as mechanical debridement and long-term antibiotic treatment, have problems with secondary infection and bacterial resistance, and lack effective non-invasive treatment methods.
By hydrothermal synthesis of Bi2S3 and graphene oxide (GO) composite materials, the interface rectification characteristics of the composite materials and the high conductivity of GO are used to activate carriers under the action of near-infrared light, promote the efficient generation of reactive oxygen species, and remove teeth Periarthritis-related microorganisms.
It has achieved efficient removal of periodontitis microorganisms, avoided bacterial resistance, had good biocompatibility and tissue repair effects, and provided a new potential means to treat periodontitis.
Smart Images

Figure CN119113112A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomaterials, and prepares an antibacterial composite material containing bismuth sulfide and graphene oxide with good biocompatibility and near-infrared light response through a simple hydrothermal synthesis method, which can resist periodontitis microbial infection. Background Art
[0002] Periodontal infection is a chronic, destructive inflammatory disease induced by bacteria that can lead to bone resorption, connective tissue destruction, and even tooth loss. More seriously, periodontitis is closely related to some systemic diseases, such as Alzheimer's disease, diabetes, cardiovascular disease, and chronic kidney disease. Clinically, mechanical debridement and adjuvant antibiotic therapy have been widely used to eliminate pathogenic microorganisms and reduce bacterial recolonization in the treatment of periodontitis. However, mechanical debridement is prone to secondary microbial infection, and long-term antibiotic treatment will destroy the patient's intestinal flora. In severe cases, it will induce bacterial resistance, posing a serious threat to the patient's recovery. Therefore, there is an urgent need for a new treatment to combat periodontitis microbial infection.
[0003] Photodynamic therapy has attracted widespread attention due to its non-invasiveness, high spatiotemporal resolution, and the fact that it does not cause bacterial resistance, making it a potentially effective measure for the treatment of periodontitis microbial infection. Generally speaking, the principle of photodynamic therapy is mainly to stimulate photosensitizers with sufficient external energy to produce photogenerated electrons and holes, which migrate to the surface of the photosensitizer and react with oxygen-containing species adsorbed by the photosensitizer to generate reactive oxygen species (ROS). Reactive oxygen species will directly act on the surface of microorganisms that cause periodontitis infection, destroy the homeostasis of microorganisms, cause microbial oxidative stress and lipid peroxidation of cell membranes, and will not induce microbial resistance mutations, ultimately achieving efficient elimination of microorganisms. Recently, with the vigorous development of photosensitizer technology, especially transition metal disulfide TMDs (Bi2S3), due to its suitable band structure (1.3-1.7 eV) and good biocompatibility, it can efficiently respond to near-infrared to achieve photothermal conversion and ROS generation. However, Bi2S3 is limited by the high recombination efficiency of photogenerated excitons, and it is usually difficult to achieve effective ROS generation under near-infrared activation, resulting in the failure of antibacterial strategies. Therefore, it is necessary to modify it. In past studies, by using two types of semiconductors with matching energy band structures to construct composite materials, the unique interface rectification properties of the composite materials were used to promote the efficient separation of photogenerated excitons, which has become an effective way to improve the insufficient ROS generation capacity of a single semiconductor. Studies have shown that two-dimensional structured graphene oxide (GO), due to its excellent biocompatibility, structural stability and high conductivity, can promote the efficient separation of photogenerated excitons, thereby improving the efficiency of ROS generation.
[0004] Therefore, the present invention firstly utilizes hydrothermal synthesis of Bi2S3, and then utilizes the oxygen-containing functional groups on the surface of GO, and uses electrostatic adsorption to obtain composite materials containing different proportions of GO and Bi2S3 (GO / Bi2S3) using Bi2S3 as a template. Under the action of near-infrared light, Bi3S2 and GO are simultaneously activated to generate photogenerated carriers. At this time, due to the interface rectification characteristics of the composite material and the high conductivity of GO, efficient separation of carriers across the interface is achieved, thereby promoting the explosive generation of ROS, achieving the purpose of quickly removing periodontal bacterial infection. Summary of the invention
[0005] The purpose of the present invention is to design and develop an antibacterial composite material composed of Bi2S3 and GO, which is used to effectively remove microorganisms related to periodontitis infection and promote tissue repair, as surgical debridement and antibiotic treatment cannot effectively cure periodontitis microbial infection and are easy to induce bacterial resistance. The present invention also provides a method for preparing the above material: first, Bi2S3 is obtained by hydrothermal reaction, and then Bi2S3 is used as a substrate to load GO in different proportions by bottom-up means. The above material has good biocompatibility and strong ability to fight periodontitis infection-related microorganisms, and can be used to treat periodontitis microbial infection and promote tissue regeneration.
[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a composite material for resisting periodontitis microbial infection, the steps comprising: (1) Preparation of Bi2S3: Weigh 1.5 g of L-cysteine and 2.5 g of bismuth nitrate pentahydrate, add them into 10 mL of deionized water respectively, and evenly disperse the solutes in the solution; then, pour the solution into the polytetrafluoroethylene lining of the hydrothermal reactor, add 40 mL of deionized water, put the inner liner into the stainless steel outer liner and tighten it, place the hydrothermal reactor in an explosion-proof drying oven, and perform hydrothermal reaction at 150°C for 24 h; after the reactor is naturally cooled to room temperature, pour the solution in the lining into a centrifuge tube and centrifuge at 8000 rpm for 10 min; the product obtained by centrifugation is ultrasonically washed three times with 30 mL of anhydrous ethanol, and the centrifugal speed and time during the washing process are the same as the first time; the washed product is dispersed with anhydrous ethanol, dried at 60°C in a drying oven to obtain a dark gray powder, and the product is collected in an EP tube and stored in a -20°C refrigerator away from light; (2) Preparation of GO: Weigh 1 g of graphite powder, add 50 mL of concentrated sulfuric acid to the graphite powder in an ice bath, and slowly add 5 mL of phosphoric acid; in an ice bath, gradually add 6 g of potassium permanganate. After the addition is complete, remove the ice bath and raise the reaction temperature to 35-40°C and stir for 2 h; add 100 mL of deionized water and then 10 mL of hydrogen peroxide. The reaction solution turns brown; repeatedly wash the reaction mixture with deionized water, separate the solid by centrifugation, and repeatedly wash until the pH is close to neutral. Finally, dry the solid powder in a 60°C oven for later use; (3) Preparation of GO / Bi2S3 composite materials: According to the mass ratio of the theoretical yield of Bi2S3 to GO of 30:1, 3 g of Bi2S3 and 0.18 GO were weighed and placed in 50 mL of deionized water respectively. The mixture was ultrasonically treated for 1 h. The gray-black powder was collected by filtration and dried in an oven at 60 °C. Finally, it was stored in a refrigerator at -20 °C away from light.
[0007] In the above technical scheme, the GO surface is rich in oxygen-containing functional groups such as carboxyl, hydroxyl and carbonyl, which can physically and chemically combine with sulfur elements and hydroxyl groups on the surface of Bi2S3.
[0008] In the above technical solution of the present invention, Bi2S3 and GO are combined to form an antibacterial composite material. Through the close interface contact between GO with metal-like properties and Bi2S3, the interfacial charge distribution of the composite material is regulated, and the light-activated carrier separation efficiency of Bi2S3 is enhanced. At the same time, due to the oxygen-rich functional groups on the surface of GO, the adsorption of oxygen-containing species is enhanced, and ROS can be efficiently generated even in the weak oxygen microenvironment of periodontal infection, thereby enhancing its performance against periodontitis microbial infection.
[0009] The beneficial technical effect of the present invention is: the present invention overcomes the lack of effective treatment methods for existing periodontitis microbial infections, and prepares Bi2S3 / GO antibacterial composite materials by a simple hydrothermal method, which are used to combat periodontitis microbial infections. The construction of the Bi2S3 / GO composite material not only strengthens the photoelectric properties of Bi2S3, promotes the effective separation of photogenerated carriers, but also enhances the adsorption of oxygen-containing species in the periodontal weak oxygen microenvironment, and realizes the efficient generation of ROS. Under the synergistic effect of multiple ROS, microbial metabolism and redox homeostasis are effectively interfered, resulting in efficient removal of microorganisms. In addition, the Bi2S3 / GO antibacterial composite material has good biocompatibility. Therefore, it has great application prospects in the treatment of periodontitis microbial infections. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0011] Figure 1 This is a scanning electron microscope (SEM) image of the material prepared in Example 1, in which the images represent layered graphene oxide (A), microspherical Bi2S3 (B), and the Bi2S3 / GO composite antibacterial material uniformly distributed on layered GO (C).
[0012] Figure 2 The photodynamic performance diagram of the materials prepared in Example 1, where A and B are the UV-visible absorption spectra of methylene blue (MB) produced by various materials under non-illumination and illumination, respectively; C and D are the UV-visible absorption spectra of methylene blue (MB) produced by various materials under non-illumination and illumination conditions. 1 UV-visible absorption spectrum of the reaction of O2 with 1,3-diphenylisobenzofuran (DPBF).
[0013] Figure 3 The antibacterial effects of different samples after light exposure, A is the antibacterial effect diagram of Fusobacterium nucleatum (Fn), and B is the antibacterial effect diagram of Porphyromonas gingivalis (Pg).
[0014] Figure 4 This is the cell activity after co-culture of the material prepared in Example 1 with periodontal ligament cells.
[0015] Figure 5 This is a diagram showing the in vivo animal antibacterial experimental effect of the material prepared in Example 1.
[0016] The symbols and materials in the above figure are: Bi2S3-bismuth sulfide, GO-graphene oxide, Bi2S3 / GO-composite material formed by combining Bi2S3 and GO, Fn-Fusobacterium nucleatum, Pg-Porphyromonas gingivalis, NIR(+)-1.0 W / cm 2 Light treatment, NIR(-)-no light treatment. DETAILED DESCRIPTION
[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Example 1
[0019] (1) Preparation of Bi2S3: First, weigh 1.5 g of L-cysteine and 2.5 g of bismuth nitrate pentahydrate, add them to 10 mL of deionized water respectively, and ultrasonically treat for 1 h to evenly disperse the solute in the solution; then, pour the solution into the polytetrafluoroethylene lining of the hydrothermal reactor, add 40 mL of deionized water, put the inner liner into the stainless steel outer liner and tighten it, place the hydrothermal reactor in an explosion-proof drying oven, and perform hydrothermal reaction at 150°C for 24 h; after the reactor is naturally cooled to room temperature, pour the solution in the lining into a centrifuge tube and centrifuge at 8000 rpm for 10 min; the product obtained by centrifugation is ultrasonically washed three times with 30 mL of anhydrous ethanol, and the centrifugal speed and time during the washing process are the same as the first time; the washed product is dispersed with anhydrous ethanol and dried at 60°C in a drying oven to obtain a dark gray powder, which is collected in an EP tube and stored in a -20°C refrigerator away from light; (2) Preparation of GO: First, weigh 1 g of graphite powder; under ice bath conditions, add 50 mL of concentrated sulfuric acid to the graphite powder, and slowly add 5 mL of phosphoric acid to improve the oxidation efficiency and reduce the formation of by-products; under ice bath conditions, gradually add 6 g of potassium permanganate. After the addition is completed, remove the ice bath and raise the reaction temperature to 35-40°C and stir for 2 h; add 100 mL of deionized water, and then add 10 mL of hydrogen peroxide (30%). The reaction solution turns brown, and surface oxide graphene is successfully prepared; the reaction mixture is repeatedly washed with deionized water, and the solid is separated using a centrifuge. Repeated washing until the pH is close to neutral, and finally the solid powder is placed in a 60°C oven to dry for later use; (3) Preparation of Bi2S3 / GO composite materials: According to the mass ratio of the theoretical yield of Bi2S3 to GO of 10:1, 3 g Bi2S3 and 0.3 g GO were weighed and placed in 50 mL centrifuge tubes respectively. The tubes were ultrasonically treated for 1 h. The gray-black powder was collected by filtration and dried in a 60 °C oven. Finally, it was stored in a -20 °C refrigerator away from light.
[0020] The scanning electron microscope (SEM) results of the prepared materials are as follows Figure 1 As shown, 1A is GO, which is a two-dimensional lamellar structure; 1B is Bi2S3, which is a spherical nanostructure; 1C is a Bi2S3 / GO composite material, in which Bi2S3 is evenly distributed on the surface of GO.
[0021] Example 2
[0022] (1) Preparation of Bi2S3: First, weigh 1.5 g of L-cysteine and 2.5 g of bismuth nitrate pentahydrate, add them to 10 mL of deionized water respectively, and ultrasonically treat for 1 h to evenly disperse the solute in the solution; then, pour the solution into the polytetrafluoroethylene lining of the hydrothermal reactor, add 40 mL of deionized water, put the inner liner into the stainless steel outer liner and tighten it, place the hydrothermal reactor in an explosion-proof drying oven, and perform hydrothermal reaction at 150°C for 24 h; after the reactor is naturally cooled to room temperature, pour the solution in the lining into a centrifuge tube and centrifuge at 8000 rpm for 10 min; the product obtained by centrifugation is ultrasonically washed three times with 30 mL of anhydrous ethanol, and the centrifugal speed and time during the washing process are the same as the first time; the washed product is dispersed with anhydrous ethanol and dried at 60°C in a drying oven to obtain a dark gray powder, which is collected in an EP tube and stored in a -20°C refrigerator away from light; (2) Preparation of GO: First, weigh 1 g of graphite powder; under ice bath conditions, add 50 mL of concentrated sulfuric acid to the graphite powder, and slowly add 5 mL of phosphoric acid to improve the oxidation efficiency and reduce the formation of by-products; under ice bath conditions, gradually add 6 g of potassium permanganate. After the addition is completed, remove the ice bath and raise the reaction temperature to 35-40°C and stir for 2 h; add 100 mL of deionized water, and then add 10 mL of hydrogen peroxide (30%). The reaction solution turns brown, and surface oxide graphene is successfully prepared; the reaction mixture is repeatedly washed with deionized water, and the solid is separated using a centrifuge. Repeated washing until the pH is close to neutral, and finally the solid powder is placed in a 60°C oven to dry for later use; (3) Preparation of Bi2S3 / GO composite materials: According to the mass ratio of the theoretical yield of Bi2S3 to GO of 20:1, 3 g of Bi2S3 and 0.15 g of GO were weighed and placed in 50 mL centrifuge tubes respectively. The tubes were ultrasonically treated for 1 h. The gray-black powder was collected by filtration and placed in an oven at 60 °C for drying. Finally, it was stored in a refrigerator at -20 °C away from light.
[0023] Example 3
[0024] (1) Preparation of Bi2S3: First, weigh 1.5 g of L-cysteine and 2.5 g of bismuth nitrate pentahydrate, add them to 10 mL of deionized water respectively, and ultrasonically treat for 1 h to evenly disperse the solute in the solution; then, pour the solution into the polytetrafluoroethylene lining of the hydrothermal reactor, add 40 mL of deionized water, put the inner liner into the stainless steel outer liner and tighten it, place the hydrothermal reactor in an explosion-proof drying oven, and perform hydrothermal reaction at 150°C for 24 h; after the reactor is naturally cooled to room temperature, pour the solution in the lining into a centrifuge tube and centrifuge at 8000 rpm for 10 min; the product obtained by centrifugation is ultrasonically washed three times with 30 mL of anhydrous ethanol, and the centrifugal speed and time during the washing process are the same as the first time; the washed product is dispersed with anhydrous ethanol and dried at 60°C in a drying oven to obtain a dark gray powder, which is collected in an EP tube and stored in a -20°C refrigerator away from light; (2) Preparation of GO: First, weigh 1 g of graphite powder; under ice bath conditions, add 50 mL of concentrated sulfuric acid to the graphite powder, and slowly add 5 mL of phosphoric acid to improve the oxidation efficiency and reduce the formation of by-products; under ice bath conditions, gradually add 6 g of potassium permanganate. After the addition is completed, remove the ice bath and raise the reaction temperature to 35-40°C and stir for 2 h; add 100 mL of deionized water, and then add 10 mL of hydrogen peroxide (30%). The reaction solution turns brown, and surface oxide graphene is successfully prepared; the reaction mixture is repeatedly washed with deionized water, and the solid is separated using a centrifuge. Repeated washing until the pH is close to neutral, and finally the solid powder is placed in a 60°C oven to dry for later use; (3) Preparation of Bi2S3 / GO composite materials: According to the mass ratio of the theoretical yield of Bi2S3 to GO of 30:1, 3 g of Bi2S3 and 0.1 g of GO were weighed and placed in 50 mL centrifuge tubes respectively. The tubes were ultrasonically treated for 1 h. The gray-black powder was collected by filtration and dried in a 60 °C oven. Finally, it was stored in a -20 °C refrigerator away from light.
[0025] Reactive oxygen release experiment Experiment 1: Weigh different groups of samples prepared in Example 1 and place them in a 48-well plate. PBS was used as the control group. MB solution (100 mL, 1 mM) and 2 mL of deionized water were mixed to a final sample concentration of 200 μg / mL. The samples were treated with 808 nm near-infrared light for 10 min (1.0 W / cm 2 ), the absorbance of the solution was determined using the UV-Vis absorbance method, and the test results are shown in Figure 2 B, the experimental results of the non-illumination group are shown in Figure 2 A.
[0026] Experiment 2: Weigh different groups of samples prepared in Example 1 and place them in a 48-well plate. PBS was used as the control group. DPBF solution (100 μL, 2 mM) was mixed with 2 mL of deionized water. The final concentration of the sample was 200 μg / mL. The samples were treated with 808 nm near-infrared light for 10 minutes (1.0 W / cm 2 ), the absorbance of the solution was determined using the UV-Vis absorbance method, and the test results are shown in Figure 2 D, the experimental results of the non-illumination group are shown in Figure 2 C.
[0027] Experimental results: From Figure 2 It can be seen that compared with Bi2S3 and GO, Bi2S3 / GO is more conducive to the production of reactive oxygen under near-infrared light excitation conditions, so as to achieve better antibacterial effect.
[0028] Antibacterial experiment Experiment 1: The materials prepared in Example 1 (Bi2S3, GO and Bi2S3 / GO) were placed in a 48-well plate. The sample concentration was 200 μg / mL. PBS was used as the control group. 100 μL of liquid culture medium and 100 μL of 10 6 CFU / mL Fusobacterium nucleatum, three parallel experimental groups were set up. Each group of samples was exposed to near-infrared light stimulation (1.0 W / cm 2 After culturing for 10 min under dark conditions, 50 μL of bacterial solution was evenly coated on the solid culture medium. After culturing at 37°C for 24 h, the bactericidal effects of various materials were observed. The experimental results are shown in Figure 3 A.
[0029] Experiment 2: Fusobacterium nucleatum (FN) was replaced with Porphyromonas gingivalis (Pg). The same method as above was used to obtain the antibacterial effects of each material on Porphyromonas gingivalis. Figure 3 B.
[0030] Experimental results: From Figure 3 It can be seen that Bi2S3 / GO can effectively produce reactive oxygen species to inhibit the growth of bacteria under near-infrared light excitation, while Bi2S3 and GO have limited inhibitory effects on bacterial growth. Therefore, Bi2S3 / GO has a good antibacterial effect under near-infrared light excitation.
[0031] Biosafety (cytotoxicity) evaluation experiment MC3T3-E1 mouse embryonic osteoblast precursor cells were cultured in DMEM containing 10% fetal bovine serum. After the cells adhered to the wall and grew, fresh culture medium was replaced. When the cells reached 80% aggregation, the cells were cultured for 10 4 / well was inoculated on a 48-well plate and cultured for 24 h. Then the cells were inoculated into a 48-well plate containing the materials prepared in Example 1 (Bi2S3, GO and Bi2S3 / GO; solubility was 200 mg / mL), with PBS as the control group, and three parallel groups were set up in each group, and cultured again for 24 h. The CCK-8 kit was used to detect the biocompatibility of the material, and the absorbance of each group was measured by an ELISA instrument at a wavelength of 450 nm, where the absorbance represents the cell activity.
[0032] Experimental results: From Figure 4 It can be seen that there is no significant difference in the cell activity of Bi2S3 / GO compared with that of other groups, which proves its excellent biocompatibility.
[0033] In vivo assay analysis: Experiment 1: Establishment of periodontitis microbial infection model This study used male Sprague-Dawley rats. First, after the rats were anesthetized, a sterile nylon ligature was placed at the cervical margin of the mandibular anterior teeth. A mixed bacterial suspension (Fn and Pg, in a 1:1 ratio, with a concentration of 1×10 8 , 0.02 mL) was injected into the mandibular incisors and observed for 3 days. The mice were fed with syrup (100 g / L -1 ) to enhance and accelerate the establishment of the inflammation model. After the model was successfully established, the inflammatory response was enhanced with or without light irradiation (808 nm, W / cm 2 , 15min), and 0.2 mL of sample PBS solution was injected into the infection site in each group.
[0034] Experiment 2: Restorative treatment of periodontitis microbial infection After the model was established, 0.2 mL (200 mg / mL) of each sample was injected into the infection site at a wavelength of 808 nm and an intensity of 1.0 W / cm 2 The rats were irradiated with a laser transmitter for 15 min. After the second week, the rats were killed to evaluate the antibacterial effect and periodontal infection repair.
[0035] Experimental results: From Figure 5 It can be seen that after the periodontitis microbial infection in the PBS group alone, the mice's gums showed obvious redness, swelling and abscesses, the gaps between teeth became larger, and the gums retracted; while in the Bi2S3 / GO group, the periodontitis infection was effectively controlled, the redness and swelling of the gums subsided, and no obvious abscesses were observed.
[0036] In summary, the Bi2S3 / GO composite antibacterial material has excellent bactericidal effect under near-infrared stimulation. At the same time, it shortens the body's inflammatory response stage during the repair process and significantly improves oral health. The present invention solves the lack of effective means to combat periodontitis microbial infection in clinical applications.
[0037] Finally, it should be noted that the above embodiments are only used to illustrate rather than limit the technical solutions of the present invention. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the present invention can still be modified or replaced by equivalents. Any modification or partial replacement that does not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.
Claims
1. Use of a composite material for combating periodontitis microbial infection in the preparation of a drug for treating periodontitis microbial infection, characterized in that: The steps for preparing the composite material for resisting periodontitis microbial infection include: (1) Preparation of Bi2S3: Weigh 1.5 g of L-cysteine and 2.5 g of bismuth nitrate pentahydrate, add them into 10 mL of deionized water respectively, and evenly disperse the solutes in the solution; then, pour the solution into the polytetrafluoroethylene lining of the hydrothermal reactor, add 40 mL of deionized water, put the inner liner into the stainless steel outer liner and tighten it, place the hydrothermal reactor in an explosion-proof drying oven, and perform hydrothermal reaction at 150°C for 24 h; after the reactor is naturally cooled to room temperature, pour the solution in the lining into a centrifuge tube and centrifuge at 8000 rpm for 10 min; the product obtained by centrifugation is ultrasonically washed three times with 30 mL of anhydrous ethanol, and the centrifugal speed and time during the washing process are the same as the first time; the washed product is dispersed with anhydrous ethanol, dried at 60°C in a drying oven to obtain a dark gray powder, and the product is collected in an EP tube and stored in a -20°C refrigerator away from light; (2) Preparation of GO: Weigh 1 g of graphite powder, add 50 mL of concentrated sulfuric acid to the graphite powder in an ice bath, and slowly add 5 mL of phosphoric acid; in an ice bath, gradually add 6 g of potassium permanganate. After the addition is complete, remove the ice bath and raise the reaction temperature to 35-40°C and stir for 2 h; add 100 mL of deionized water and then 10 mL of hydrogen peroxide. The reaction solution turns brown; repeatedly wash the reaction mixture with deionized water, separate the solid by centrifugation, and repeatedly wash until the pH is close to neutral. Finally, dry the solid powder in a 60°C oven for later use; (3) Preparation of GO / Bi2S3 composite materials: According to the mass ratio of the theoretical yield of Bi2S3 to GO of 30:1, 3 g of Bi2S3 and 0.18 GO were weighed and placed in 50 mL of deionized water respectively. The mixture was ultrasonically treated for 1 h. The gray-black powder was collected by filtration and dried in an oven at 60 °C. Finally, it was stored in a refrigerator at -20 °C away from light.
Citation Information
Patent Citations
Preparation method of grapheme and ferriferrous oxide composite nanometer material
CN103274396A
Sulfide coated particle as well as preparation method and application thereof
CN107983272A
Bi2S3-MoS2 / graphene composite nano material and preparation method thereof
CN110247038A
